ANALISIS PENGARUH BEBAN KERJA TERHADAP KINERJA PETUGAS ADMINISTRASI DI RUMAH SAKIT PANAM - Anastasya Shinta Yuliana; Wiwik Suryandartiwi; Aditya, Frigita Selly (Journal of Hospital Administration and Management (JHAM), 2023)
The effect of workload is the impact of excessive workload which results in an unfavorable impact on the performance of hospital administrative officers, which will cause fatigue both physically and mentally. At Awal Bros Panam Hospital, which is crowded with patient visits every day, the burden on administrative staff increases and causes human errors. This study aims to determine the effect of workload on the performance of administrative officers at the early bros panam hospital. This type of research is qualitative with an analytical descriptive approach.is supported by an empirical juridical approach. The study was conducted on 18 July-18 August 2022 at Awal Bros Panam Hospital. There were 8 informants in the study and the research used a Content Analysis model. The results showed that shifts that are prone to errors in data input are the morning shift, no special training for administrative officers, no rewards from the hospital, no backup computers, no display of SOPs related to administrative officers, no regular machine maintenance. It can be concluded that the effect of workload on the performance of administrative officers affects the performance of officers. It is recommended that there be additional officers on the morning shift, special training such as SIMRS training for administrative officers on a regular basis, giving rewards from the hospital, providing backup computers, displaying SOPs related to administrative officers and doing regular machine maintenance. Keywords : Influence Workload, Performance, Administrative Officer